Application Of The Principle Of Freedom Of Contract In Business Contracts In Indonesia - Irmanto Brampu; Henry Aspan; H. Dahlan (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
The Indonesian business community is currently developing very rapidly, and the number of business transactions in Indonesia has also increased. This situation shows that the Indonesian economy is very favorable for people who want to do business in Indonesia, not only Indonesian entrepreneurs but also foreign entrepreneurs. A legal principle applies to the agreement, namely the principle of freedom of contract, which declares a person's freedom to enter into a contract in a conditional form. As long as the parties agree and does not violate etiquette and law, the agreement will be valid. . The research method used is the normative legal approach, which is the analysis and understanding of law within the framework of this study as a set of positive rules or norms in a legal system that governs human life. This was done by studying books, laws, regulations and other documents relevant to this study. In addition, the collection of legal materials also includes legal material analysis methods and legal analysis methods that adjust should be, as long as this is the method of measuring and analyzing the issues in this study. The application of the principle of freedom of commercial contract requires the parties to maintain a balanced position when formulating agreements regulating commercial legal relationships. If a balance is not achieved, economic actors will limit and avoid liability by including release clauses. It is therefore necessary for the government to intervene to limit the application of the principle of freedom of contract through standard contracts by establishing rules prohibiting the inclusion of exemption clauses and monitoring the use of standard clauses in the economy by economic operators.